Property rights attitudes are a source of public opposition to flood mitigation policies in the United States. Issue 3 (27th August 2021) - Strother, Logan; Hatcher, Laura
Abstract: Floods are the costliest disasters in American history—and today, floods are getting both worse and more common. As flooding becomes ever more salient one might expect that public support for flood prevention and mitigation policies would grow, yet we see significant opposition to a wide range of flood policies. We find, across four samples and a range of study designs and measurement strategies, that citizens are more likely to oppose flood mitigation policies when they think the policy in question will harm someone's property rights. This finding has important real‐world implications, as many policy proposals aimed at addressing flood disasters, including approaches as diverse as floodwater diversion and elimination of flood insurance subsidies, can infringe on property rights and interests. This study highlights one tension in addressing flood policy in democratically acceptable ways, and also the important effects that framing can have on mass support for flood mitigation policies. 摘要: 洪灾是美国历史上代价最大的灾害—如今，洪灾正在恶化和变得更频繁。鉴于洪灾事件变得日益显著，公民可能会期望洪灾预防及缓解政策所获得的公共支持将增加，不过，实际则是出现了对一系列防洪政策的大量抵制。通过四个样本和一系列研究设计及测量策略，我们发现，当公民认为洪灾缓解政策将损害他人的财产权时，他们更有可能反对这类政策。该研究发现具有重要的现实意义，因为许多致力应对洪灾的政策提议（包括分洪和洪灾保险补助取消等多种措施）可能侵犯财产权和相关利益。本研究强调了以民主可接受的方式应对洪灾政策时出现的紧张关系，并强调了建构可能对洪灾缓解政策的大众支持产生的重要效果。 Resumen: Las inundaciones son los desastres más costosos en la historia de Estados Unidos y, en la actualidad, las inundaciones son cada vez más frecuentes y peores. A medida que las inundaciones se vuelven cada vez más importantes, uno podría esperar que el apoyo público a las políticas de prevención y mitigación de inundaciones crezca, pero vemos una oposición significativa a una amplia gama de políticas de inundaciones. Encontramos, a través de cuatro muestras y una variedad de diseños de estudios y estrategias de medición, que es más probable que los ciudadanos se opongan a las políticas de mitigación de inundaciones cuando piensan que la política en cuestión dañará los derechos de propiedad de alguien. Este hallazgo tiene importantes implicaciones en el mundo real, ya que muchas propuestas de políticas destinadas a abordar los desastres por inundaciones, incluidos enfoques tan diversos como el desvío de aguas de inundación y la eliminación de los subsidios de seguros contra inundaciones, pueden infringir los derechos e intereses de propiedad. Esta investigación destaca una tensión al abordar la política de inundaciones de formas democráticamente aceptables, y también los importantes efectos que el encuadre puede tener en el apoyo masivo a las políticas de mitigación de inundaciones.